Motivasi kerja karyawan perusahaan: Adakah peranan dari kepemimpinan transformasional dan clan culture? - Made Benyta Kristina; Eko April Ariyanto; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between transformational leadership and clan culture with work motivation at company X located in Surabaya. This research is a correlational study that aims to identify the relationship between transformational leadership and organizational culture and work motivation. Participants in this study were 130 employees from company X in the Surabaya area with an age range of 24-50 years, male and female. This research technique is a saturated sampling technique in which all the population will be sampled. The data collection method was carried out by distributing questionnaires online via the Google form using a Likert scale. Data analysis used multiple linear regression testing techniques with the help of the SPSS computer program. The results show that there is no relationship between transformational leadership and organizational culture on work motivation. Meaning that this proves that transformational leadership and clan culture have no impact on employee motivation. In other words, the lower the transformational leadership style and clan culture, the lower the employee's work motivation. Keywords: Work motivation, Transformational leadership, Clan culture